The Case for an EU-NATO Hybrid Centre of Excellence in the Indo-Pacific - Abbondanza, Gabriele (My University, 2025)
.

The commentary argues that the Indo-Pacific has become a major arena for hybrid threats, including cyberattacks, disinformation, cognitive warfare, economic coercion, proxy conflict, and attacks below the threshold of open war. It reviews recent examples across the region, such as China’s pressure on Taiwan, pandemic-era disinformation, India-Pakistan tensions, foreign interference in New Caledonia, and emerging risks in space. Against this background, the author explains how both NATO and the EU have developed tools to respond to hybrid threats, and proposes creating a new EU-NATO Hybrid Centre of Excellence in the Indo-Pacific. The piece suggests that Australia would be the best host because of its strong ties with NATO, growing links with the EU, regional experience, and advanced cyber capabilities.
Artículos en revistas